Blockade of Opioid Receptors Located in the Rat Nucleus Cuneiformis Reduced the Antinociceptive Responses of Local But not Systemic Administration of Morphine in Formalin Test - Abbas Haghparast (Basic and Clinical Neuroscience, 2010)
ABSTRACTPrevious studies have shown the role of opioid receptors located in the nucleus cuneiformis (CnF) in acute pain, but not in chronic pain models. In the present study, we have determined that possible effects of these receptors at the CnF on both early and late phases of formalin test following local and systemic morphine administration. Each rat was given a subcutaneous 50-μl injection of 2.5% formalin into plantar surface of hind paw. Ninety five Wistar rats bilaterally received morphine (1, 2, 4 and 8 μg/0.3 μl saline per side) into the CnF, just before the formalin test. Naloxone (1 μg/0.3 μl saline per side) was also microinjected 2 minutes before local or 28 minutes after intraperitoneal administration of morphine. The results showed that bilateral intra-CnF administration of morphine dose-dependently produced analgesia in formalin test. Naloxone administration into the CnF antagonized the analgesic response induced by morphine (4 μg/0.3 μl saline) microinjection. The results also showed that analgesic effect of systemic morphine was not significantly decreased by naloxone microinjection. We suggest that the opioid receptors located in the CnF, in part, indirectly affect the morphine-induced descending pain modulatory circuit.